DIGITAL TOPOGRAPHIC MODELLING IN CASE WITH HIGHER FLOOD IN THE MUNICIPALITY OBRENOVAC - Valjarević, Aleksandar; Živković, Dragica (Bulletin of Natural Sciences Research, 2018)
The town of Obrenovac is situated near the banks of three rivers, the Sava River, the Kolubara River and the Tamnava River. It looks like a modern town, though it has often developed in an unplanned manner. This causes huge problems as it thrives in a rough terrain, without a plan, which the communal infrastructure cannot follow. Today’s needs in terms of spatial planning, envisaging projects and keeping track of a different kind of information on space demand that new technologies be applied since they make it possible for procuring efficient and reliable information as well as connecting and interconnecting various sorts of data. Also with advanced numerical GIS data and relief analysis we were successfully calculated consequence of the last big flood in 2014.